Application of nanomaterials in antifouling: A review - Nan Wang; Ruiyong Zhang; Kunpeng Liu; Yuxin Zhang; Xin Shi; Wolfgang Sand; Baorong Hou (Nano Materials Science)
With the continuous development of the marine economy and the upgrading of marine infrastructure, the increasing marine engineering equipment is facing a serious problem of marine fouling. However, developing marine antifouling materials and antifouling technologies is extremely difficult due to the complexity of the marine environment and the biodiversity of the fouling. Therefore, it is the key breakthrough to develop advanced materials for solving marine fouling problems. Nanomaterials with small dimensions and controlled micro-structure have outstanding antifouling efficiency and great promise for various antifouling fields. Herein, the development of antifouling nanomaterials and technologies in recent years are reviewed for aspects of types of antifouling nanomaterials, technologies of antifouling, and potential application of antifouling. The antifouling nanomaterials are categorized as non-metal-based nanomaterials, metal-based nanomaterials, polymeric nanomaterials, composite nanomaterials, and others. Additionally, the potential applications of antifouling nanomaterials, including marine antifouling, water treatment, and medical antifouling are discussed. Finally, we proposed the perspectives of research and development trends of the antifouling nanomaterials. This overview may promote the development of new efficient antifouling nanomaterials and develop their potential commercial applications.